CONCENTRATION OF LONTAR SUGAR (Borassus flabellifer Linn) AND ITS EFFECT ON PHYSICOCHEMICAL AND ORGANOLEPTIC PROPERTIES OF VILLAGE CHICKEN JERKY - Ndia, Yelia May Danga; Ina, Yessy Tamu; Kaka, Alexander (Jurnal Pangan dan Agroindustri, 2021)
This study aims to determine the different concentrations of palm sugar on the physicochemical and organoleptic properties of chicken jerky. This study used RAL with 4 treatments and 5 replications, namely soaking chicken meat with a concentration of palm sugar 10%-40%. Observation variables were water content, pH, antioxidant and organoleptic. The data obtained include data on water content, pH and organoleptic then analyzed by ANOVA at 95% level. While the total antioxidants were tested descriptively. The results of the analysis showed that the concentration of palm sugar 10%-40% contained water content (8.52-10.52%), the concentration of palm sugar 10-40% (6.33-5.64%) The higher the concentration of palm sugar in chicken meat jerky In chicken, the lower the pH, the antioxidants produced in each treatment of palm sugar were 10% - 40% (79.28% - 83.23%) and 40% palm sugar could increase the panelists' acceptance of organoleptic.